A canonical interlaminar circuit in the sensory dorsal ventricular ridge of birds: The anatomical organization of the trigeminal pallium. Issue 14 (5th July 2021) - Fernández, Máximo; Reyes‐Pinto, Rosana; Norambuena, Carolina; Sentis, Elisa; Mpodozis, Jorge
Abstract: The dorsal ventricular ridge (DVR), which is the largest component of the avian pallium, contains discrete partitions receiving tectovisual, auditory, and trigeminal ascending projections. Recent studies have shown that the auditory and the tectovisual regions can be regarded as complexes composed of three highly interconnected layers: an internal senso‐recipient one, an intermediate afferent/efferent one, and a more external re‐entrant one. Cells located in homotopic positions in each of these layers are reciprocally linked by an interlaminar loop of axonal processes, forming columnar‐like local circuits. Whether this type of organization also extends to the trigemino‐recipient DVR is, at present, not known. This question is of interest, since afferents forming this sensory pathway, exceptional among amniotes, are not thalamic but rhombencephalic in origin. We investigated this question by placing minute injections of neural tracers into selected locations of vital slices of the chicken telencephalon. We found that neurons of the trigemino‐recipient nucleus basorostralis pallii (Bas) establish reciprocal, columnar and homotopical projections with cells located in the overlying ventral mesopallium (MV). "Column‐forming" axons originated in B and MV terminate also in the intermediate strip, the fronto‐trigeminal nidopallium (NFT), in a restricted manner. We also found that the NFT and an internal partition of B originate substantial, coarse‐topographic projections to the underlying portion of the lateral striatum. We conclude that all sensory areas of the DVR are organized according to a common neuroarchitectonic motif, which bears a striking resemblance to that of the radial/laminar intrinsic circuits of the sensory cortices of mammals. Abstract : The avian dorsal telencephalon contains discrete areas receiving visual, auditory, and trigeminal ascending projections. Recent studies have shown that the auditory and the visual regions embodied "columnar and layered" cytoarchitectural motifs, which bears a striking resemblance to that of the mammalian sensory cortices. At present, it is not known to what extent this type of organization also extends to the trigemino‐recipient area. The question is of interest, since afferents forming this sensory pathway are exceptionally not thalamic but rhombencephalic in origin. We investigated this question by placing minute injections of neural tracers into selected locations of vital slices of the chicken telencephalon. We conclude that the trigeminal area share, to a detailed level, a common columnar‐layered neuroarchitectectonic motif with other sensory areas.